Convective Mass/Heat Analysis of an Electroosmotic Peristaltic Flow of Ionic Liquid in a Symmetric Porous Microchannel with Soret and Dufour. (28th June 2021) - Yasmin, Humaira; Iqbal, Naveed
Abstract : This research deals with the mathematical model for the development of the peristaltic principle of the combination of the pressure and electroosmotic flow (EOF) of ionic liquid across microchannels with electrokinetic effects. For thermomechanical dynamics, the convective conditions on the boundary for mass and heat transfer at the walls of the channel are quantified. For the microchannel, a porous structure is presumed. Soret, Dufour, and Joule heating are also listed in the scope of the problem addressed. The corresponding equations for the ionic fluid flow, mass, and heat transfer along with the Poisson–Boltzmann equation within the electrical double layer (EDL) are studied. The exact solution has been obtained based on lubrication theory (i.e., low Reynolds number and long wavelength approximations). The channel height is therefore believed to be much higher than the electrical double layer (EDL) thickness. Various dimensionless pertinent parameters illustrate the important aspects of electroosmotically controlled flow and subsequent convective mass/heat transfer attributes in a microchannel. A linear dependency on the fluid flow rate is exhibited by the pressure drop. The analysis shows that the electroosmotic parameter gives a reducing effect on the channel permeability. The distribution of temperature and concentration is greatly affected by convective heat and mass parameters, respectively. In biomedical engineering, the application areas of the study proposed are for the design of the devices such as a microfluidic pump to pump a small amount of ionic liquids by regulating the variation in temperature and concentration.